Economic Impact of the Implementation of a PCDT for Cow Protein Allergy – CMPA in the State of Rio Grande do Norte - dos Santos de Oliveira, Bruno; Bezerra Pires, João Marcos; Vieira da Silva, Thiago Augusto; Assunção Costa, Lindemberg; Camargo, Erica (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Introduction: Cow’s milk protein allergy (CMPA) is one of the most common food aller gies in childhood, affecting children under 3 years old. In Brazil, prevalence ranges from 1% to 5.4%, with a significant impact on the Unified Health System (SUS) due to the high costs of special formulas used in treatment. The implementation of Clinical Protocols and Therapeutic Guidelines (CPTG) has proven to be an efficient strategy for managing CMPA. Objective: To report the experiences of the state of Rio Grande do Norte in implementing the CPTG for CMPA and to analyze the economic impact associated with providing special formulas. Methods: This descriptive study was based on data from government reports and scientific literature from 2019 to 2023. Costs related to the provision of special formulas and the impact of the COVID-19 pandemic on demand were evaluated. The analysis included historical trends in care and inflation-adjusted econo mic calculations. Results: From 2019 to 2023, there was an increase in the demand for special formulas and associated costs, driven by the pandemic and price volatility. However, administrative strategies reduced costs related to judicial demands by up to 50%. In 2023, 595 patients were enrolled in state programs, with significant growth in coverage and treatment access. Conclusion: The implementation of public policies such as CPTGs for CMPA in the Rio Grande do Norte proved cost-effective, expanding access and optimizing public spending. Investments in early diagnosis and efficient administra tive management are essential to improve clinical and economic outcomes.